CHILDHOOD NEPHROTIC SYNDROME IN KADUNA STATE (1985)
The clinicopathological features of childhood nephritic syndrome in tropical Africa are different from those in temperate countries of Europe and America. However, detailed clinicopathological features of the disease have not been comprehensively described in all parts of Africa. Plasmodium malariae has been shown to be strongly associated with the disease in some parts of Africa, and the association has been postulated to be causal. Childhood nephrotic syndrome was studied in Kaduna State of Nigeria in an attempt to define the clinicopathological features of the disease. In particular, the study set out to assess the role of P. malariae in the aetiology or pathogenesis of childhood nephrotic syndrome, and to look for other possible aetiological factors. One hundred consecutive children with nephrotic syndrome who had had no treatment previously were studied. In addition to routine biochemical and haematological investigations, malaria parasitaemia, protein selectivity index, serum hepatitis B surface antigen and percutaneous renal biopsy were done. As described in other parts of tropical Africa, children with nephrotic syndrome presented with massive oedema, prominent ascites, and very low serum proteins. P. malariae parasitaemia was present in 31% of nephrotic children, compared with 7% in the control group of children. The frequency of P. malariae parasitaemia was 40% in patients with membranoproliferative glomerulonephritis, 40% in quartan malarial nephropathy, and 21% in proliferative glomerolunephritis. Serum hepatitis B surface antigen was positive in the sera of 31% of patients compared with 30% in control but the concentration of antigen was stronger in the patients. Schistosoma mansoni ova were found in the stool or rectal snip of six patients: histology of renal biopsy showed membranoproliferative glomerulonephritis in four of these patients. Protein selectivity index was determined by comparing the clearances of albumin and immunoglobulin IgG. The index was good in 34% of patients. However, the test was not found useful in identifying those lesions likely to respond to corticosteroid therapy. Percutaneous rena1 biopsy was successful in 98 of the 1OO patients. By light microscopy, the most common histological diagnoses were membranopro 1iferative glomerulonephritis (25 cases), quartan malarial nephropathy (20), and proliferative glomerulonephritis (19 cases). Together they formed 65% of the biopsies. Immunofluorescence was abnormal in 92%: there were deposits of immunoglobulins, C3, P. malariae and hepatitis B surface antigen. Schistosome antigens were not looked for. Short-term prognosis of the disease was not as good as in children in Europe or North America, but did not seem to be as poor as in children studied in Ibadan. Quartan malarial nephropathy was not the predominant type of childhood nephritic syndrome seen in Kaduna State, since it accounted for less than a quarter of the cases studied. This is in contrast to the finding in Ibadan where quartan malarial nephropathy was responsible for over 80% of cases of childhood nephrotic syndrome. There was some evidence that hepatitis B surface antigen could also play a role in the aetiology or pathogenesis of the disease in Kaduna State. There is still no satisfactory treatment for childhood nephrotic syndrome in tropical Africa. Eradication or control of infectious diseases should result in reduced incidence of the disease.